Influence of polymer aging on reliability indices of a typical printed-circuit assembly of radioelectronic equipment; Journal of Engineering Physics and Thermophysics; Vol. 80, iss. 5 - Kuznetsov G. V. Geny Vladimirovich (2007, 2007)
Title screen